From cold to hot: mechanisms of hyperthermia in modulating tumor immunology for enhanced immunotherapy - Abreu, M. Marc; Chocron, Alberto F.; Smadja, David M. (Frontiers in Immunology, 2025)
The emergence of immunotherapies has revolutionized cancer treatment by leveraging the immune system to target malignancies, offering new hope where traditional therapies often fall short. Within this context, hyperthermia (HT) has re-emerged as a promising adjunctive treatment, capable of enhancing the effectiveness of radiotherapy, chemotherapy, and immunotherapy. HT influences both the innate and adaptive immune systems, enhancing the activity of immune cells such as neutrophils, NK cells, and dendritic cells, while also modulating the tumor microenvironment (TME) to promote immunogenic cell death (ICD) and reduce immunosuppressive conditions. These effects contribute to the transformation of immunologically “cold” tumors into “hot” tumors, making them more susceptible to immune-mediated destruction. Furthermore, HT can amplify the efficacy of immune checkpoint inhibitors (ICIs) by improving immune cell infiltration, inducing damage-associated molecular pattern (DAMP) release, and enhancing antigen presentation. Preclinical and clinical studies support the combination of HT with ICIs, demonstrating improved outcomes in otherwise resistant tumors. However, the full therapeutic potential of the different technologies allowing to apply HT remains to be fully understood, and further research is needed to optimize treatment protocols, explore the differential impacts of local versus whole-body hyperthermia, and identify biomarkers for patient stratification. This review underscores the multifaceted role of HT in immunity and its potential to significantly enhance the efficacy of immunotherapy.